2018
DOI: 10.3389/fncel.2018.00230
|View full text |Cite
|
Sign up to set email alerts
|

Role of CXCR1 and Interleukin-8 in Methamphetamine-Induced Neuronal Apoptosis

Abstract: Methamphetamine (METH), an extremely and widely abused illicit drug, can cause serious nervous system damage and social problems. Previous research has shown that METH use causes dopaminergic neuron apoptosis and astrocyte-related neuroinflammation. However, the relationship of astrocytes and neurons in METH-induced neurotoxicity remains unclear. We hypothesized that chemokine interleukin (IL) eight released by astrocytes and C-X-C motif chemokine receptor 1 (CXCR1) in neurons are involved in METH-induced neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 58 publications
3
38
0
Order By: Relevance
“…In this study, we found that the expression of the apoptosis‐related proteins Cleaved Caspase‐3 and Cleaved PARP was increased significantly after METH exposure, which indicated that apoptosis was increased by METH. These results are consistent with previous studies (Du et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, we found that the expression of the apoptosis‐related proteins Cleaved Caspase‐3 and Cleaved PARP was increased significantly after METH exposure, which indicated that apoptosis was increased by METH. These results are consistent with previous studies (Du et al, ; Xu et al, ).…”
Section: Discussionsupporting
confidence: 94%
“…METH is toxic to all systems of the body, especially the central nervous system (Yang et al, ). Accumulating evidence shows that METH induces apoptosis, oxidative stress, and mitochondrial dysfunction in vivo and in vitro (Du et al, ; Foroughi, Khaksari, Rahmati, Bitaraf, & Shayannia, ; Shin et al, ; Xu et al, ). Furthermore, METH can lead to the damage of dopaminergic neurons and Parkinson‐like pathology (Biagioni et al, ; Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In all, these data confirm that METH treatment elicits gliosis and neuroinflammation within cerebral organoids as indicated by enhanced IL-6 expression, overexpression of GFAP and NLRP-1. Consistent with our findings, it was recently found that neuroinflammation was induced in primary mice astrocytes and astrocytic cell lines treated with METH through the involvement of Toll-Like Receptor 4, caspase 11, and nuclear factor-Kappa B [42][43][44]. The induction of neuroinflammation resulted in neurotoxicity by upregulating cytokines IL-6 and IL-8 levels [42,44].…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study indicated that (1) serum levels of IL-6 and IL-8 were increased in MAP patients; (2) IL-2R levels had a negative correlation with the intensity of positive psychotic symptoms, but IL-6 and IL-8 levels did not; (3) cognitive dysfunction was present in the MAP patients (MOCA total scores of 26 and higher are generally considered normal); and (4) the severity of different types of cognitive impairment was positively correlated with IL-6, IL-8, and IL-10 levels. These results agree with the aforementioned findings indicating altered immune response activity in MAP patients (14)(15)(16)(17)(18).…”
Section: Discussionsupporting
confidence: 93%